Representação de suspeitos de homicídios com negativa de autoria em uma abordagem sociodiscursiva - Valdirecia de Rezende Taveira (2019)
It is known that the Media plays a fundamental role in representing social events, influencing the construction of public opinion and, in some cases, even triggering certain events, such as certain crimes of homicide, which are often reported. In this context, it is argued in the Legal area if due to the way cases of considerable repercussion are reported, certainsuspects of crimes could be already condemned by the media and, consequently, by society (media-influenced) before the legal process. Thus, taking in mind those discussions about the possibility of influence of media in criminal legal proceedings, especially those attributedto the Jury Court, as in the case of homicides, we perceived the need to understand the diverse discursive representations present in media world when reporting the occurrence of crimes, especially those with authorship denial. The main objective of our work is to demonstrate how the discursive representation of suspects of homicides with denial of authorship is reported, observing if there is a discursive orientation that attributes the authorship and the guilty to the suspects before the Legal process. We elected for the present study the death event of the girl Isabella Nardoni, occurred in 2008, and that one of the model Eliza Samúdio, occurred in 2010. Our corpus consists of 9 (nine) texts published in Veja magazine, during the time of investigation about the two events. Our theoretical framework is anchored in Social Semiotics (HODGE E KRESS, 1988; VAN LEEUWEN, 2005) and authors and theories that dialog with it, such as the Multimodality approach(KRESS & VAN LEEUWEN, 1996, 2006) and the Appraisal System (MARTIN & WHITE, 2005; MARTIN & ROSE, 2007) as they are presented as social theories of discourse that allow us to reflect about language and discursive practices in contemporary society. We propose, therefore, to carry out a sociodiscursive analysis, observing whether,from the different semiotic modes employed, there is a guilty representation of those involved and/or if a previous condemnation is implied in the discourse. Our analysis point to an argumentative orientation in which the suspects, even before the Legal process evenstarted, seem to be prejudged and the authorship of the crimes are attributed to the suspects, prior to the conclusion of the investigations. In both cases it is explicit, from the different semiotic modes that, in the analyzed texts, potential meanings are produced leading to a representation of the suspects as probable agents of the crimes, which was the focus of this research. In the case of Isabella Nardoni, the suspects are represented by a negative point of view, emphasizing behaviors reprehensible by society, in which the association ofthe various semiotic modes allows the reader to construct a negative image of them, taking with it, in this image of murderers. In the same way, in the case of the murder of Eliza Samúdio, the interrelationship of the semiotic resources employed lead to the attribution of authorship of crime, especially Bruno Fernandes, the main suspect of this crime. In thiscase, the textual elements, presents a strong intermodal integration allowing to understand the potential meaning of killer, associating the suspect directly to the murder. In addition, guilt and punishment were also pointed out in cases, since an argumentative approach callsfor punishment of the suspects.